MEMAKNAI SIMBOL TELINGA PANJANG DAYAK BAHAU BUSANG DI ZAMAN INI: Studi Analisis-Kritis Dalam Makna Simbol Menurut Ernst Cassirer - Bang, Barnabas; Saeng, Valentinus (Universitas Katolik Parahyangan, 2022)
This study aims to find out the meanings contain in the apang aruq tradition. The apang aruq tradition is a community habit to lengthen the earlobe. The process of elongating the earlobe occurs since a person is a baby until he dies. The purpose of this study is to provide readers with an understanding of the meaning of the apang aruq tradition of the Bahau Busang Dayak community in East Kalimantan Province. This study uses a qualitative approach by describing the discussion based on three guiding questions. The data collection technique used in this research is literature study, which is the activity of collecting materials related to research from cultural books and Ernst Cassirer. In this paper, the author finds that there are three functions of the apang aruq tradition, they are self-identity referring to the meaning of knowledge, beauty symbolizing the physical and metaphysical beauty of humans and as a marker of age implying space and time.